The Effects of Water Provision and Education on Students’ Hydration Status, Cognitive Abilities, and Fine Motor Function in A Full-Day Primary School - Saidah Rauf; Santi Aprilian Lestaluhu (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background/aim: Dehydration due to inadequate water intake in children may disrupt brain functions. This study aimed to investigate the effects of hydration education with water provision on hydration status, cognitive functions and motor performance. Materials and Methods: Forty-eight children in primary full-day school (age 8 – 11 years) were recruited in this study. The intervention of hydration education was performed for two days, both for students and teachers. The water was provision for 12 days. Letter cancellation task (LCT), symbol digit modalities test (SDMT), and direct image different test (DIDT) were used to assess cognitive functions. Motor performance was evaluated using a finger tapping test (FTT). Hydration status was determined with urine specific gravity (USG) and urine color (UC). Before and after interventions, all parameters were evaluated.Results: Most students found dehydrated (>65%). The students had lower USG and UC after the intervention and it was correlated with each other (before; rs=0.45, P = 0.001 and after; rs=0.82, P = 0.001). All cognitive and motor functions were significantly higher after an intervention (P < 0.05). Conclusion: Hydration education to students and teachers combined with water provision at primary full-day school increases hydration status and enhances cognitive and fine motor skills.